Gestational diabetes mellitus and associated risk factors among pregnant women in Tuaran, Sabah State, Malaysia - Dr Swe; Herwati Dualis; Mohammad Saffree Jeffree; Khamisah Awang Lukman; Mohd Yusof Ibrahim; Fredie Robinson; Naing Oo Tha; Firdaus Hayati; Syed Sharizman Syed Abdul Rahim (Türkiye Klinikleri, 2020)
Objective: To determine the prevalence of gestational diabetes mellitus (GDM) and its associated risk factors among pregnant women in Tuaran District, Sabah State, Malaysia. Material and Methods: A cross sectional analytical study was conducted in Tuaran. Data collection was done by interview method using structured questionnaire and antenatal records review. The study population was all the pregnant women, at and above 24 weeks of gestation who attended the antenatal care clinics in Tuaran District from March to June, 2018. The pregnant women with pre-existing diabetes were excluded from the study. Convenience sampling method was used and 195 pregnant women participated in the study. Descriptive and analytical statistics were done by using SPSS statistical software. GDM has emerged as a major public health concern all over the world. It would develop maternal and foetal adverse outcomes. The prevalence of GDM ranged from 1% to 28% worldwide and from 18.3% to 27.9% in Malaysia.